2021
DOI: 10.1021/acscatal.1c04541
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Formal [4 + 3] Annulations to Access Benzodiazepinones and Benzoxazepinones via NHC/Ir/Urea Catalysis

Abstract: A robust and scalable formal [4 + 3] annulation reaction for the synthesis of optically pure 1,4-benzodiazepinones and 1,4-benzoxazepinones has been established by a combined catalytic system consisting of a chiral NHC, a chiral Ir/phosphine-olefin complex, and an achiral urea, enabling the asymmetric synthesis of a selective inhibitor of mitochondrial F1F0 ATP hydrolase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…A variety of chiral 7-membered heterocycles 28 were successfully constructed in good yields with high enantioselectivities (Scheme 6). 35 The addition of achiral urea OC1 dramatically enhanced the stereocontrol, possibly owing to cooperative catalysis with the chiral NHC. A plausible mechanism is proposed below.…”
Section: π-Allyl-m-type Mcrdsmentioning
confidence: 99%
“…A variety of chiral 7-membered heterocycles 28 were successfully constructed in good yields with high enantioselectivities (Scheme 6). 35 The addition of achiral urea OC1 dramatically enhanced the stereocontrol, possibly owing to cooperative catalysis with the chiral NHC. A plausible mechanism is proposed below.…”
Section: π-Allyl-m-type Mcrdsmentioning
confidence: 99%
“…N-Heterocyclic carbene (NHC)-mediated umpolung reactivity of aldehydes has enabled numerous highly significant reactions. In recent years, NHC/transition metal cooperative catalysis has shown its robustness in creating new transformations and hence has received increasing attention. Within this context, azolium homoenolate/enolate intermediates catalytically generated from NHC and carbonyls can be successfully captured by electrophiles activated by ruthenium, palladium, iridium, ,, copper, , gold, and nickel complexes, leading to synthetically useful transformations and a greater understanding of reaction manifolds possibly occurring with NHC/TM cooperative catalysis. More recently, our group demonstrated that isatin-derived homoenolate equivalent I (Figure A) governs the geometry, facial selectivity, and regioselectivity of the oxindole moiety in a stereodivergent propargylic alkylation reaction .…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the extensively explored Pd, Ir, or Ni-π-allyl species, as well as Cu-allenylidene species, coupling with chiral NHC-adorned nucleophiles, asymmetric reactions mediated by other types of electrophilic TM-activated intermediates, however, is still comprehensively elusive in this area. Recently, our group ( 50 , 55 58 ) demonstrated that the isatin-derived homoenolate equivalent I ( 60 63 ) exhibits high facial selectivity and good feasibility with metal-activated electrophiles, providing an important advance to access synthetically valuable oxindole derivatives ( Fig. 1C ).…”
Section: Introductionmentioning
confidence: 99%